Respuesta :

Answer:

[tex]\int \:3\cdot \frac{x}{\left(x-1\right)^2}dx=3\left(\ln \left|x-1\right|-\frac{1}{x-1}\right)+C[/tex]

Step-by-step explanation:

Given

[tex]\int \:\:3\cdot \frac{x}{\left(x-1\right)^2}dx[/tex]

[tex]\mathrm{Take\:the\:constant\:out}:\quad \int a\cdot f\left(x\right)dx=a\cdot \int f\left(x\right)dx[/tex]

[tex]=3\cdot \int \frac{x}{\left(x-1\right)^2}dx[/tex]

[tex]\mathrm{Apply\:u-substitution:}\:u=x-1[/tex]

[tex]=3\cdot \int \frac{u+1}{u^2}du[/tex]

[tex]\mathrm{Expand}\:\frac{u+1}{u^2}:\quad \frac{1}{u}+\frac{1}{u^2}[/tex]

[tex]=3\cdot \int \frac{1}{u}+\frac{1}{u^2}du[/tex]

[tex]\mathrm{Apply\:the\:Sum\:Rule}:\quad \int f\left(x\right)\pm g\left(x\right)dx=\int f\left(x\right)dx\pm \int g\left(x\right)dx[/tex]

[tex]=3\left(\int \frac{1}{u}du+\int \frac{1}{u^2}du\right)[/tex]

as

[tex]\int \frac{1}{u}du=\ln \left|u\right|[/tex]     ∵ [tex]\mathrm{Use\:the\:common\:integral}:\quad \int \frac{1}{u}du=\ln \left(\left|u\right|\right)[/tex]

[tex]\int \frac{1}{u^2}du=-\frac{1}{u}[/tex]        ∵     [tex]\mathrm{Apply\:the\:Power\:Rule}:\quad \int x^adx=\frac{x^{a+1}}{a+1},\:\quad \:a\ne -1[/tex]

so

[tex]=3\left(\ln \left|u\right|-\frac{1}{u}\right)[/tex]

[tex]\mathrm{Substitute\:back}\:u=x-1[/tex]

[tex]=3\left(\ln \left|x-1\right|-\frac{1}{x-1}\right)[/tex]

[tex]\mathrm{Add\:a\:constant\:to\:the\:solution}[/tex]

[tex]=3\left(\ln \left|x-1\right|-\frac{1}{x-1}\right)+C[/tex]

Therefore,

[tex]\int \:3\cdot \frac{x}{\left(x-1\right)^2}dx=3\left(\ln \left|x-1\right|-\frac{1}{x-1}\right)+C[/tex]